Pharmacokinetics and pharmacodynamics of oral dexamethasone in healthy horses - Grady, Jason A. (Kansas State University, 2008)
Objective: To determine pharmacokinetic and pharmacodynamic properties of oral dexamethasone solution and powder compared to intravenous dexamethasone solution in healthy horses. Animals: 6 horses, 13-27 years if age, 385-630 kg Procedures: In a randomized, cross-over block design six healthy adult horses each received the following treatments 1) dexamethasone solution IV 0.05 mg/kg, 2) dexamethasone solution orally (PO) 0.05 mg/kg, and 3) dexamethasone powder PO 0.05 mg/kg all in the fed and fasted state. Each horse acted as an untreated control as secretion of cortisol was monitored for normal circadian rhythm. Quantification of plasma dexamethasone concentration and serum cortisol activity was determined by LC/MS and chemiluminescent enzyme immunoassay, respectively. Results: Each horse exhibited a circadian rhythm in cortisol secretion; however there was variation present between each horse. Mean cortisol concentrations at 6:00 AM and 8:00 AM were significantly higher than concentrations at 8:00 PM and 10:00PM. Cortisol concentrations were significantly less than base-line starting 1 hour post-administration of dexamethasone through 72 hours for the fasted treatment groups, and 2 hours through 48 hours for the fed groups. Pharmacokinetic modeling resulted in a two compartment model for the IV administration with elimination from the central compartment, and a one compartment model for orally administered dexamethasone. Oral, fasted, compounded powder achieved a significantly higher maximum concentration (Cmax) than both fasted and fed oral dexamethasone solutions. The AUC0inf for the orally administered compounded powder was significantly different when comparing fasted versus fed treatment groups. Bioavailability ranged between 33% and 70% among treatment groups, but due to the high variability there was not a significant difference. Conclusions and Clinical Relevance: Hospitalization of the horses did not have an effect on their circadian rhythm of cortisol secretion. Oral and intravenous administration of dexamethasone resulted in adrenal suppression with cortisol concentrations returning to base-line 48-72 hours post-administration. Although bioavailability was variable cortisol suppression was similar among all treatment groups. The variability in oral absorption will need to be taken in to account for oral dosing of dexamethasone.
Keywords: Veterinary; Pharmacokinetics; Pharmacodynamics; Dexamethasone; Pharmacology; Horse; Biology, Veterinary Science (0778)